2013
DOI: 10.1186/2008-2231-21-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the effects of fluoxetine and imipramine on total cholesterol, triglyceride, and weight in patients with major depression

Abstract: BackgroundThere are some reports on the effects of antidepressants on metabolic syndrome. However, our search in the previously published literature showed a lack of information on the comparison of the effects of different classes of antidepressants on lipid profile. Therefore, this study was aimed to compare the effects of fluoxetine and imipramine on serum total cholesterol (TC) and triglyceride (TG) as well as body weight (BW) in patients with major depressive disorder.MethodsFifty one patients, 18 to 70 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…The present work emphasizes the improvement of metabolic and vascular effects induced by DM and CRS with chronic fluoxetine treatment in contrast to no improvement or even worsening of these effects with imipramine. Several previous studies have reported the favorable effect of chronic fluoxetine treatment on blood glucose and lipids [ 41 , 42 ]; this effect may be due to improvement of insulin sensitivity which is noticed in this work, fluoxetine also have an antioxidant effect [ 43 ]. Breum et al [ 44 ] reported that chronic fluoxetine treatment improved glycemic control in patients with NIDDM with improvement of insulin sensitivity.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The present work emphasizes the improvement of metabolic and vascular effects induced by DM and CRS with chronic fluoxetine treatment in contrast to no improvement or even worsening of these effects with imipramine. Several previous studies have reported the favorable effect of chronic fluoxetine treatment on blood glucose and lipids [ 41 , 42 ]; this effect may be due to improvement of insulin sensitivity which is noticed in this work, fluoxetine also have an antioxidant effect [ 43 ]. Breum et al [ 44 ] reported that chronic fluoxetine treatment improved glycemic control in patients with NIDDM with improvement of insulin sensitivity.…”
Section: Discussionsupporting
confidence: 54%
“…Moreover, Ghaeli et al [ 41 ] and Salehi and Sanjani [ 52 ] revealed increase in fasting blood glucose upon chronic treatment with imipramine. Ananloo et al [ 42 ] reported increased serum total cholesterol, triglyceride and body weight in depressive patients treated with imipramine. Indeed, previous reports revealed imipramine-induced dyslipidemia, insulin resistance and endothelial dysfunction in CMS model [ 53 ], but this is the first study showing this observation in CRS paradigm.…”
Section: Discussionmentioning
confidence: 99%
“…One of these four compounds, dronedarone (S2114), is used in therapy for the treatment of patients with paroxysmal and persistent arterial fibrillation or atrial flutter 46 . The second compound, tofranil (SAM002564216), a strong serotonin reuptake blocker, is mainly used in the treatment of depression 47 . The third compound, bendrofluazide (SAM002264598), is used for treatment of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Flu enhanced the insulin sensitivity in obese patients and ameliorated the function of pancreatic β-cell secretory in drug-naive major depressive disorder (MDD) patients6566. In addition, when it came to TC and TG, data showed that both of the parameters were decreased by chronic Flu treatment in patients with MDD67. Partially in line with Met (1.8 mg/kg, i.p), Flu (10.8 mg/kg, i.p) and MF, HFD-STZ-induced effects on PG (Fig.…”
Section: Discussionmentioning
confidence: 99%